2018
DOI: 10.31219/osf.io/2td84
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Socioeconomic status and the susceptibility to overeat from excessive food portions

Abstract: Acknowledgments:We thank Léo Dutriaux for providing feedback on an earlier draft of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Thus, another aim of the present research was to examine the moderating effects of family socioeconomic status on SSB and water intake. Recently, we showed that adults with a lower socioeconomic status are more susceptible to the food portion-size effect, partly because lower socioeconomic status was associated with finding larger portions more appropriate (8).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, another aim of the present research was to examine the moderating effects of family socioeconomic status on SSB and water intake. Recently, we showed that adults with a lower socioeconomic status are more susceptible to the food portion-size effect, partly because lower socioeconomic status was associated with finding larger portions more appropriate (8).…”
Section: Introductionmentioning
confidence: 99%